The Influence of Circular Fashion, Narrative Branding, and Social Activism on the Competitiveness of Sustainable Fashion MSMEs in West Java - Ikmalul Miftah Zainutthalibien (Sciences du Nord Economics and Business, 2025)
This study examines the influence of circular fashion, narrative branding, and social activism on the competitiveness of sustainable fashion MSMEs in West Java. Using a quantitative approach, survey data were collected from 175 MSME owners, managers, and production leaders engaged in sustainable fashion practices. All constructs were measured using a five-point Likert scale, and the data were analyzed using SPSS version 25 through descriptive statistics, validity and reliability testing, classical assumption tests, and multiple regression analysis. The findings reveal that circular fashion has the strongest positive effect on competitiveness, indicating that upcycling, recycling, and resource-efficient processes significantly enhance product value and differentiation. Narrative branding also contributes meaningfully, demonstrating that authentic storytelling and value-based communication increase brand loyalty and market distinction. Social activism further strengthens competitiveness by building trust, legitimacy, and deeper engagement with socially conscious consumers. Collectively, the three independent variables explain 62.9% of the variance in MSME competitiveness. The study concludes that sustainable production practices, compelling narratives, and social engagement are essential strategic drivers for strengthening the competitive performance of sustainable fashion MSMEs in West Java. These findings offer practical guidance for MSME practitioners and reinforce the importance of sustainability-focused strategies within the creative economy.